The relationship between tax revenues and economic growth in Libya during the period (1990-2018) - Bileid جمعة; Sasi عمر; Alzawam السنوسي (Journal of Pure & Applied Sciences, 2024)
The study aimed to measure the relationship between tax revenues and economic growth in Libya during the period (1990-2018), using the standard approach to estimate the relationship between the study variables, Using the ARDL. the study concluded that there is a co-integration relationship in the long term between tax revenues and economic growth, and that tax revenues have a negative impact on economic growth, but the effect not significant at 5%.